La resistencia palestina: praxis no violenta desde un paradigma gramsciano (2020)
This article analyses the praxis of nonviolent resistance in Palestine through the lens of Gramsci. First, it begins with a historical inquiry into the major phenomena of the Palestinian resistance tradition. Its nonviolent expressions are highlighted in order to prove their continuity as well as their effectiveness, focusing on three uprisings of the national movement where this form of resistance was deployed: the Arab revolt, the First Intifada, and the Al Aqsa Intifada. Then, it presents the framework of the theoretical tradition of nonviolent struggle in order to interpret Palestinian popular resistance actions and strategies. Finally, these forms of resistance are embedded, and subsumed, in a Gramscian alternative hegemonic paradigm, so as to enhance the discussion around an organic nonviolent strategy of political resistance.